An Empirical Study On The Influence Of Islamic Values On Money Demand (Case Study: University of Darussalam, Gontor and Mantingan Campus) - Muhammad Fahmi Jauharuddin Rimas Sude; Khoirul Umam (Islamic Economics Journal, 2018)
Chapra thought about money demand contains Islamic Values. The research on Chapra’s money demand has been done by some researchers such as Ebrinda and Sri Wahyuni, both researchers are in macro level, and the results of Ebrinda’s research is that social values have not significant effect on Islamic money demand in Indonesia and limit her research on social values, while the results of Sri Wahyuni’s research is that social values have not significant effect on money demand in the short term and significant effect in the long term. From here the researcher try to examine the effect of Islamic values on money demand in micro level at University of Darussalam Gontor, in addition to the pesantren system also has high Islamic values. The purpose of this study is to determine the effect of Islamic values on money demand from micro perspective. This research is quantitative research. In data collection, the researcher uses a questionnaire method. The data is analyzed by multiple linear regression method. The method is used to predict the value of a dependent variable based on the values of two or more variables. The results of research is that Islamic values have not significant effect on money demand. It’s proven by significance level which is still more than 0.05. The significance level of needs is 0.4, social values is 0.7, wasteful spending is 0.3 and savings is 0.3. While the variables that have significant effect are income with significance level 0.00, investment 0.00, and presupposition investment 0.04.